2021
DOI: 10.3344/kjp.2021.34.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Headache related to mask use of healthcare workers in COVID-19 pandemic

Abstract: This study indicates that healthcare workers develop headaches due to use of masks during the COVID-19 outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…The incidence of PPE-associated headaches amongst healthcare workers in the context of the COVID-19 pandemic ranges from 26.5%–90.7% [ 24 , 25 ••, 26 – 32 , 33 •, 34 •, 35 •, 36 •]. In comparison, a study amongst healthcare providers using the N95 face mask during the 2003 severe acute respiratory distress syndrome (SARS) epidemic in Singapore observed that new-onset face mask–associated headaches occurred with an incidence of 37.3% [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…The incidence of PPE-associated headaches amongst healthcare workers in the context of the COVID-19 pandemic ranges from 26.5%–90.7% [ 24 , 25 ••, 26 – 32 , 33 •, 34 •, 35 •, 36 •]. In comparison, a study amongst healthcare providers using the N95 face mask during the 2003 severe acute respiratory distress syndrome (SARS) epidemic in Singapore observed that new-onset face mask–associated headaches occurred with an incidence of 37.3% [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Since the start of COVID-19 in December 2019, there have been a total of 6 published studies specifically conducted to understand PPE-associated headache amongst healthcare workers (see Table 1 ) [ 25 ••, 33 •, 34 •, 35 •, 36 •, 38 •]. Based on these studies, several factors have been found to confer a greater likelihood of developing de novo PPE-associated headaches.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations